2015
DOI: 10.4082/kjfm.2015.36.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Lymphoma Kinase-Positive Anaplastic Large Cell Lymphoma Arising in a Patient with Hypersensitivity to Mosquito Bites

Abstract: Hypersensitivity to mosquito bites is defined as the appearance of intense skin reactive lesions and systemic symptoms subsequent to mosquito bites. Most cases of hypersensitivity to mosquito bites reported thus far have been associated with chronic Epstein-Barr virus infection or natural killer cell leukemia/lymphoma. In this study, we describe the case of an 18-year-old Korean boy who had hypersensitivity to mosquito bites associated with primary systemic anaplastic lymphoma kinase-positive anaplastic large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“… 10 , 11 Exceptionally, HMB in patients with mantle cell lymphoma, 12 nodal marginal zone lymphoma, 13 Hodgkin lymphoma, 14 chronic myeloid leukemia, 15 and primary systemic anaplastic lymphoma kinase-positive anaplastic large-cell lymphoma have been reported. 16 The mechanism inducing lymphoma development following a mosquito bite is still not fully clarified. Previous studies have shown that mosquito salivary gland extracts promote CD4+ T cells proliferation, and induce expression of the viral oncogene latent membrane protein (LMP1) in NK cells via mosquito antigen-specific CD4+ T cells, which is involved in the oncogenesis of NK cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Exceptionally, HMB in patients with mantle cell lymphoma, 12 nodal marginal zone lymphoma, 13 Hodgkin lymphoma, 14 chronic myeloid leukemia, 15 and primary systemic anaplastic lymphoma kinase-positive anaplastic large-cell lymphoma have been reported. 16 The mechanism inducing lymphoma development following a mosquito bite is still not fully clarified. Previous studies have shown that mosquito salivary gland extracts promote CD4+ T cells proliferation, and induce expression of the viral oncogene latent membrane protein (LMP1) in NK cells via mosquito antigen-specific CD4+ T cells, which is involved in the oncogenesis of NK cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Disease and medication associations may offer insight into PC‐ALCL pathogenesis. PC‐ALCL has been linked to atopic dermatitis, mosquito bite hypersensitivity, hemophagocytic lymphohistiocytosis and a paraneoplastic syndrome of inappropriate antidiuretic hormone with tumor cells showing antidiuretic hormone expression . Other disease associations include case reports of chronic myelogenous leukemia in remission, keratosis lichenoides chronica and squamous cell carcinoma .…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…However, mosquito bite has been reported to trigger anaplastic lymphoma, kinase-positive anaplastic large-cell lymphoma, nodal marginal zone lymphoma, and mantle-cell lymphoma, originating from T-cell or B-cell. [678] The mosquito bite was significantly related to morbidity in the children with HVLL. [9] These two cases of HVLL also had an obvious history of hypersensitivity to mosquito bite.…”
Section: Discussionmentioning
confidence: 99%